(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
القصيدة عند نزار قبَّاني ذات طموح محدود، لأنَّه حوَّل الحب إلى عمل بيولوجي، ونزع منه المشاعر الإنسانيَّة والتَّضحية واستخدام خليطاً لونيَّاً عجيباً لا يدلُّ على حسٍّ فنِّي، وقد سوَّغ عمله لأنَّه كان في حالة عدم الوعي، ويكون ذلك قد أعفى ناقده من اختيار وصف لهذه الحال. ولقد كانت الألوان التي استخدمها خاصَّة بنوع محدَّد من النساء، فالنموذج الجمالي لديه هو النَّموذج الغربي، لذلك استخدم كل الألوان التي تناسب ذلك النموذج، وكانت الغاية من إضفاء الألوان للإيقاع بالمرأة عن طريق الكلام المعسول الذي يدور في مجالس المراهقين. لقد بقي نزار قباني وفيَّاً للمدرسة الرومانسيَّة التي ينتمي إليها وللطبقات البرجوازيَّة التي تهتمُّ بالمرأة من أجل أن تتخذها وسيلة لإرواء الملذَّات وترويج السلع بالإضافة إلى الذاتية والنرجسيَّة. ولو أراد الناقد أن يختزن عيوب أشعار نزار قبَّاني في كلمات قليلة لقال إنَّ شعر الغزل عنده هو عبارة عن قصيدة غزليَّة واحدة استمرَّ الشَّاعر مكرراً إياها على مدى نصف قرن أو يزيد. The poem of the Syrian poet, Nizar Qabbani is limited ambition, because he changed love into a biological act. He empties it of human feelings and devotion; and he uses a very strange colourful mixture, which dose not indicate an artistic sense. He justifies his work as being in a state of unconsciousness; thus saving his critics the trouble of looking for a term to describe this situation. The colours he uses are characteristic of special kind of women. His aesthetic type is a western one. Therefore, he uses all the colours which suit that type. The objective of this colouring is to seduce woman by sweet words, which take place in the company of teenagers. Nizar remains faithful to the romantic school he belongs to, and faithful to the bourgeois classes which are interested in woman as a means of satisfying desires and promoting goods, in addition to being a sign of the individualism and narcissism of those classes. If a critic wanted to summarize the flaws of Nizar Qabbaani’s verses in a few words, he would put it this way, “His amorous (erotic) verse is only one, single amorous poem, which he keeps repeating over again for more than half a century.